Beyond the screen: The psychological significance of ecophilia in childhood - Asha S; Vineeth Radhakrishnan (MethodsX)
The environmental crisis, fuelled by rapid urbanization, technology, and changing lifestyles, threatens humanity. Children's disconnection from nature negatively impacts their physical, mental, and environmental well-being, increasing their risk of psychological distress, including elevated stress levels, impaired emotional stability and cognitive function, diminished social interactions, and increased susceptibility to anxiety, depression, lower self-esteem, and reduced overall life satisfaction. Consequently, environmental risks have impact on the health and development of the children from early childhood to adolescence and then to adult life. The research article aims at diminished nature connection in children and the emergence of psychological distress. This interdisciplinary research, blending ecology and psychology, uses ecocritical lenses—biophilia (love for nature and living things), topophilia (love for particular place or environment), and ecophilia (love for nature itself) —to explore how diminished nature connection impacts children's well-being. The findings emphasize the importance of reconnecting children with nature and fostering ecospirituality for their well-being and a sustainable future. This research concludes that fostering ecophilia enhances children's cognitive function, environmental awareness, and stewardship, while also promoting ecospirituality. • Human-nature interactions are key learnings for children. • This research aims to integrate ecology and psychology fostering interdisciplinary approach.